Reduced Adverbial Clause In English - Rakhmasari, Dwi Lia (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
Human cannot communicate with one another without language. Good language will affect the effectiveness of the information delivery. Using a good adverb clause is one of effective sentence example. However, the continuous use of adverb clauses will also create redundancies in the delivery of information. Therefore, it is necessary to have a variety of uses of adverb clauses, one of which is the use of reducing adverb clauses. This research provides a description of what elements that can be reduced in the Reduced Adverbial Clause and what changes that occurs in Reduced Adverbial Clause after the reduction process is carried out. The data of this research is collected from corpus with note-taking technique. This study uses qualitative methods with interactive techniques. Interactive technique covers three components, namely data reduction, data presentation and conclusion drawing. This research found that adverbial clause can be reduces as long as it has the same subject. Elements that can be reduced in adverbial clause are subject, subject and auxiliary, and conjunction. The changes of reduced clause can be in the form of present participle, past participle, and clause without subject and auxiliaries. Keywords: Reduced Adverbial Clause, Language, Adverbial Clause